1998
DOI: 10.1002/(sici)1097-4636(19980905)41:3<405::aid-jbm10>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor adsorption and release properties of calcium phosphate

Abstract: Basic fibroblast growth factor (bFGF) is well known as a potent angiogenic factor playing a crucial role in wound-healing processes. Apatitic substrates such as hydroxyapatite and carbonated apatite (CA) could be potential carriers of growth factors because of their physicochemical similarities to bone mineral. These materials have been compared for their bFGF adsorption and release properties. The adsorption of the growth factor was higher on carbonated apatite than on hydroxyapatite, probably owing to enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 19 publications
1
35
0
Order By: Relevance
“…Measurements of bFGF adsorption onto the mineralized materials suggest that a majority of bFGF was adsorbed by the graft (>80%). This is consistent with other studies that showed high levels of bFGF adsorption by the CaP-based materials [35, 36]. …”
Section: Discussionsupporting
confidence: 93%
“…Measurements of bFGF adsorption onto the mineralized materials suggest that a majority of bFGF was adsorbed by the graft (>80%). This is consistent with other studies that showed high levels of bFGF adsorption by the CaP-based materials [35, 36]. …”
Section: Discussionsupporting
confidence: 93%
“…The microstructure of materials, including roughness, microporosity and SSA, is another factor affecting protein adsorption. Midy et al proved that the higher adsorption of basic fibroblast growth factor on carbonated apatite than HA could be ascribed to the higher SSA, which gave the carbonated apatite a higher surface reactivity [43]. Suh et al reported that the amount of BSA adsorbed on silicon particles increased significantly with increasing size of the micropores, and this effect was in addition to the contribution of SSA to BSA adsorption [44].…”
Section: Discussionmentioning
confidence: 99%
“…42 Further- more, intact HAp surfaces containing carbonate groups may be potential carriers of growth factors because of their physicochemical similarities to bone mineral. 43 The HAp-coated silicone material can, therefore, be assumed to be bioactive in vivo.…”
Section: Discussionmentioning
confidence: 99%